T Cell Extracellular Traps: Tipping the Balance Between Skin Health and Disease - Ouyang, Kelsey; Oparaugo, Nicole; Nelson, Amanda M.; Agak, George W. (Frontiers in Immunology, 2022)
The involvement of extracellular traps (ETs) in the host innate immune response against pathogens is well established. ETs were first identified in neutrophils and have since been identified in several other immune cells. Although the mechanistic details are not yet fully understood, recent reports have described antigen-specific T cells producing T cell extracellular traps (TETs). Depending on their location within the cutaneous environment, TETs may be beneficial to the host by limiting the spread of pathogens, shielding against robust tissue damage, promoting early wound closure and degrading inflammatory mediators to initiate the resolution of skin inflammation. However, ETs have also been associated with worse disease outcomes. Here, we consider host-microbe ET interactions by highlighting how cutaneous T cell-derived ETs aid in orchestrating host immune responses against Cutibacterium acnes (C. acnes), a commensal skin bacterium that contributes to skin health, but is also associated with acne vulgaris and surgical infections following joint-replacement procedures. Insights on the role of the skin microbes in regulating T cell ET formation have broad implications not only in novel probiotic design for acne treatment, but also in the treatment for other chronic inflammatory skin disorders and autoimmune diseases.